A sabedoria humana de Pierre Charron: articulações entre ceticismo e estoicismo - Estefano Luis de Sa Winter (2013)
Pierre Charron (1541-1603) argues in his most influential work, De la Sagesse, an ideal of wisdom purely natural. This ideal is mainly practical and teaches man to be moderate, to master the force of passions and to amend the weakness of his nature. The wisdom proposed in the work has as its main goal to teach self-knowledge, which is the most valuable remedy for human predicaments that man can achieve through their own efforts. It is also the main mean to maintain intellectual integrity and the freedom to judge everything. As wisdom teaches self-knowing, it is the excellence and true science of man, which should be pursued by those who have a strong spirit. To support his thesis, Charron drew upon several sources, Stoic and Skeptical, of his time, by connecting and transforming these sources, he develops a concept of human wisdom and establishes its practical rules. However, due to the eclectic character of his text and the variety of sources used, there is wide controversy among interpreters concerning the best way to understand the Sagesse. Is it closer to stoicism? To skepticism? Or is it just a plagiarism of the work of Michel de Montaigne? In order to answer these questions, we examined the objectives of Charron when writing his work and the way he relates two types of skepticism (Pyrrhonism and Academic skepticism) with Stoicism, which he received mainly through the Neo-Stoic Guillaume Du Vair. Charrons reception of these three Hellenistic philosophical schools is central in one of the most relevant concepts of the work: probity (preudhomie). In the first chapter of this thesis we present Charrons work in a general way, showing its importance in the period and to what extent his concept of human wisdom should be understood as an exercise of the strong spirit that teaches self mastery (maîtrise de soi). The second chapter examines how the reception of skepticism in Sagesse has two goals, the first, Pyrrhonean, is linked to the project of self-knowledge; the second, Academic, is linked to the construction of the formal rules of wisdom, especially the concept of probability). Finally, in the last chapter we seek to identify the Stoic influences in Charrons thought and the way in which the concept of probity (preud'homie), inspired by the Neo-stoicism of Du Vair, integrates with elements of Academic skepticism, working as a bridge that connects and makes coherent the Skepticism and the Stoicism present in the work. We conclude that the Pyrrhonean moment in the Sagesse prepares the ground, the Academic moment establishes the contours and that the Stoic moment shapes and establishes the content of the work. The three moments are combined into a single concept, that of probity (preud'homie), which is the main foundation of Charrons wisdom.